CD8‐positive cutaneous lymphoproliferation associated with large granular lymphocyte leukemia in a patient with X‐linked agammaglobulinemia. (30th September 2020) - Daou, Hala; Hatch, Leigh A.; Weinkle, Allison; Morey, Gabriel Eli; Messina, Jane; Zhang, Xiaohui; Sokol, Lubomir; Seminario‐Vidal, Lucia
Abstract: Patients with primary immunodeficiency are at increased risk for malignancy, especially hematologic neoplasms. This paper reports a unique case of a 47‐year‐old man with X‐linked agammaglobulinemia who presented with progressive asymptomatic violaceous papules and plaques on his face, hands, and trunk for 1 year. Skin biopsies revealed deep, nodular infiltrates of histiocytes and CD8‐positive lymphocytes, with a CD4:CD8 ratio of 1:10. Laboratory studies showed cytopenias. Flow cytometry in the skin, blood, and bone marrow (BM) showed a CD3+/CD8+/CD57+ large granular lymphocyte population. BM biopsy showed 30% involvement with these atypical T‐cells. T‐cell gene rearrangement studies of skin, blood, and BM revealed identical T‐cell clones. He was diagnosed with T‐large granular lymphocyte leukemia (T‐LGLL) with an associated CD8+ cutaneous lymphoproliferation. Skin involvement was suspected to represent infiltration by T‐LGLL. However, co‐existence of two lymphoproliferative disorders (LPDs), T‐LGLL and CD8+ granulomatous LPD, remains a possibility. In general, cutaneous infiltrates associated with LGLL are rare and poorly understood. It has been suggested that they are markers of poor prognosis. Our case report describes skin, blood, and BM findings in an immunosuppressed patient with T‐LGLL in detail. These findings have not yet been reported and their significance requires further investigation.